Antimicrobial Resistance of Listeria monocytogenes from Animal Foods to First- and Second-Line Drugs in the Treatment of Listeriosis from 2008 to 2021: A Systematic Review and Meta-Analysis - Jaqueline Oliveira Dos Reis; Bruno Serpa Vieira; Adelino Cunha Neto; Vinicius Silva Castro; Eduardo Eustáquio de Souza Figueiredo (Canadian Journal of Infectious Diseases and Medical Microbiology)
First-line drugs for the treatment of listeriosis are the same around the world, but particular conditions might reduce their efficacy, including antimicrobial resistance. Therefore, this study aimed to verify, based on a systematic review and meta-analysis, whether the prevalence of antimicrobial resistance in Listeria monocytogenes from animal foods is higher for first- or second-line antimicrobials. From the total of 302 identified studies, 16 met all the eligibility criteria from 2008 to 2021 and were included in this meta-analysis. They comprised a dataset of 1152 L. monocytogenes isolates, obtained from different animal food products, food processing environment, and live animals. The included studies were developed in South America (n = 5), Europe (n = 4), Asia (n = 3), Africa (n = 2), and North America (n = 2), testing a total of 35 different antimicrobials, 11 of them classified as first-line drugs. Complete lack of antimicrobial resistance across the studies (all L. monocytogenes isolates tested as susceptible) was only observed for linezolid, while widespread antimicrobial resistance (all L. monocytogenes isolates tested resistant) was described for amoxicillin, benzylpenicillin, cefoxitin, fusidic acid, imipenem, sulfamethoxazole, and vancomycin. Overall, the meta-analysis results indicated no evidence that antimicrobial resistance in L. monocytogenes isolated from animal-based food is higher for first-line antimicrobials compared to second-line compounds (p=0.37). A greater volume of publication, together with better characterization of the isolates, is still needed for a more precise estimate of the real prevalence of antimicrobial resistance in L. monocytogenes.